2014
DOI: 10.1103/physrevlett.113.065301
|View full text |Cite
|
Sign up to set email alerts
|

Motion of a Solitonic Vortex in the BEC-BCS Crossover

Abstract: We observe a long-lived solitary wave in a superfluid Fermi gas of 6 Li atoms after phase imprinting. Tomographic imaging reveals the excitation to be a solitonic vortex, oriented transverse to the long axis of the cigar-shaped atom cloud. The precessional motion of the vortex is directly observed, and its period is measured as a function of the chemical potential in the BEC-BCS crossover. The long period and the correspondingly large ratio of the inertial to the bare mass of the vortex are in good agreement w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
193
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(204 citation statements)
references
References 44 publications
(75 reference statements)
11
193
0
Order By: Relevance
“…The latter, in particular, opens up an interesting way to study the snake instability in twocomponent condensates, in the same manner as it is currently being the case of DS decay in scalar condensates [45,46]. Besides, the decay of JVs in SO coupled condensates provides an excellent playground to investigate the rich dynamics of vortex dipoles as has been previously done in scalar BECs [47,48].…”
Section: Discussionmentioning
confidence: 92%
“…The latter, in particular, opens up an interesting way to study the snake instability in twocomponent condensates, in the same manner as it is currently being the case of DS decay in scalar condensates [45,46]. Besides, the decay of JVs in SO coupled condensates provides an excellent playground to investigate the rich dynamics of vortex dipoles as has been previously done in scalar BECs [47,48].…”
Section: Discussionmentioning
confidence: 92%
“…A similar procedure was applied in a superfluid Fermi mixture [21] resulting in a local disturbance of the atomic density which oscillated in an harmonic trap much more slowly than predicted for a dark soliton [22][23][24]. In a recent experiment [25] it has been shown that the state created by means of the phase imprinting method evolves very quickly to a so-called vortex soliton -see also theoretical analysis in Refs. [26,27].…”
mentioning
confidence: 99%
“…The family of BEC solitons consists of many interesting members, from bright solitons in attractive BECs [6] and gap solitons in optical lattices [7], to dark solitons in repulsively interacting BECs [3][4][5], which are created experimentally by imprinting a sharp and characteristic phase jump into the BEC. Remarkably, dark solitons may also be created in strongly interacting Fermi gases [8][9][10][11][12][13][14][15][16] at the crossover from BECs to Bardeen-Cooper-Schrieffer (BCS) superfluids [17], where phase kinks are encoded in the pairing order parameter. Their recent experimental observation may offer valuable insights into the nature of fermionic superfluidity in the strongly correlated regime [13,18].…”
mentioning
confidence: 99%
“…1 is easy to set up [22,28], although the realization of 1D topological superfluids is difficult due to the lack of efficient cooling techniques [22]. Majorana solitons can be created by imprinting a sharp phase jump [13,15]. The observation of their oscillations seems to be an experimental challenge, as the density profile of Majorana solitons remains flat [26,27].…”
mentioning
confidence: 99%